2009
DOI: 10.1523/jneurosci.0888-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Laminin Alters Fyn Regulatory Mechanisms and Promotes Oligodendrocyte Development

Abstract: Mutations in LAMA2, the gene for the extracellular matrix protein laminin-␣2, cause a severe muscular dystrophy termed congenital muscular dystrophy type-1A (MDC1A). MDC1A patients have accompanying CNS neural dysplasias and white matter abnormalities for which the underlying mechanisms remain unknown. Here, we report that in laminin-deficient mice, oligodendrocyte development was delayed such that oligodendrocyte progenitors accumulated inappropriately in adult brains. Conversely, laminin substrates were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 37 publications
6
89
0
Order By: Relevance
“…The degree of developmental delay is region-specific, which may reflect different laminin a2 requirements ). Abnormalities in Fyn signaling, which is modulated by laminins in cultured oligodendrocytes, were observed in the mutant brains, suggesting one explanation for the temporary stall in oligodendrocyte differentiation (Colognato et al 2004;Relucio et al 2009). Interestingly, b1 integrins not only affect PNS but also CNS myelination (Relvas et al 2001;Barros et al 2009).…”
Section: Lamininsmentioning
confidence: 95%
See 1 more Smart Citation
“…The degree of developmental delay is region-specific, which may reflect different laminin a2 requirements ). Abnormalities in Fyn signaling, which is modulated by laminins in cultured oligodendrocytes, were observed in the mutant brains, suggesting one explanation for the temporary stall in oligodendrocyte differentiation (Colognato et al 2004;Relucio et al 2009). Interestingly, b1 integrins not only affect PNS but also CNS myelination (Relvas et al 2001;Barros et al 2009).…”
Section: Lamininsmentioning
confidence: 95%
“…Expression of laminins correlates with the onset of CNS myelination (Colognato et al 2002;Colognato et al 2005), and varied degrees of defects have been found in white matter tracts of patients suffering from MDC (Caro et al 1999;Leite et al 2005). Mice lacking laminin a2 have a developmental delay in oligodendrocyte maturation, resulting in hypomyelination (Chun et al 2003;Relucio et al 2009). The degree of developmental delay is region-specific, which may reflect different laminin a2 requirements ).…”
Section: Lamininsmentioning
confidence: 99%
“…The identification of regulators of actin polymerization suggests a direct effect of Wnt signaling on SC process extension and lamellipodia formation. In particular, Fyn kinase has been shown to control cytoskeletal modifications and lamellae extension in oligodendrocytes (44,45). The identified transcription factors could also directly affect SC differentiation: Jun is a known negative regulator of SC differentiation and myelination (2,46).…”
Section: Mechanisms Of Axonal Sorting Deficits In β-Catenin Mutant Scmentioning
confidence: 99%
“…exo, exosomes. (26,(33)(34)(35)(36)(37)(38). We used the small molecular inhibitor PP2 to find out whether NCM increase oligodendrocytes cell surface area in a Src kinase-dependent manner.…”
Section: Elination Exosomes Were Isolated From ϳ10mentioning
confidence: 99%